Kecerdasan Buatan dan Keberlanjutan Sosial: Tinjauan Literatur tentang Dampak Teknologi Kemanusiaan dalam Pendidikan - Yulisia Rezky Kirana; Nurfadillah Salam; Riakurnaini; Hasrinah; Arifah Novia Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of artificial intelligence (AI) has made a significant contribution to the transformation of global education, particularly in increasing the effectiveness, personalization, and efficiency of the learning process. However, behind this progress, new challenges have emerged related to the shift in human values, the loss of empathy, and the potential for dehumanization in education. This article aims to systematically review the relationship between AI, humanity, and social sustainability in education through the Systematic Literature Review (SLR) method with the PRISMA approach. Data were obtained from 480 Scopus-indexed publications (2020–2025) with the keywords